Analisis Pelepasan (drop out) Sunat Modern Super Ring Dengan Berbagai Intervensi Pada Anak Sunat di Ponorogo - Nanang Saputro Agung Widodo; Heri Saputro; Saifulah, Dedi (Journal of Health Science Community, 2022)
Modern methods as circumcision that are more effective with minimal pain are clamp circumcision, electric cauter, CO2 laser. The purpose of this study was to determine the effectiveness of removing the circumcision apparatus by soaking in warm water and applying aloe vera gel to children in Ponorogo. This research method uses a quantitative approach with the type of research experimental design. The sample in this study were 28 people. The sampling technique used was simple random sampling. The results of the study from 28 samples, it was found that the removal of the circumcision apparatus by soaking in warm water in most children was 8 respondents (57%) 10 days, most of the removal of circumcision tools with aloe vera gel smeared (aloe vera) 12 respondents (86%) < 10 days. The results of the independent T-test analysis showed that the statistical test results obtained a Sig value (2 tailed) or a p value of 0.011 and 0.012 where <0.05. Because <0.05, the difference in effectiveness is statistically significant or significant at a probability of 0.05. The magnitude of the difference in the mean or mean of the two groups is shown in the mean difference column, which is 1.35714. Modern wound care techniques have the advantage of increasing granulation growth so that wounds heal quickly, have good healing qualities and can reduce wound care costs.